Future-proofing the EU's investment attractiveness: A bold reform agenda for competition enforcement, taxation and digital policy - Matthias Bauer; Dyuti Pandya; Oscar du Roy (European Centre for International Political Economy (ECIPE), 2024)
Reducing the deterrent effects from EU and Member State laws in three key cross-sector policy areas - competition policy, business taxes and VAT, and digital policies - could significantly enhance the business environment within the Single Market and boost the EU's attractiveness to both domestic and foreign investors. The EU's future competitiveness is at risk due to a significant disparity in investments, particularly in technological innovation, compared to the US. Despite having a larger population and labour force, the EU lags behind in large business activities, with US firms consistently outspending their European counterparts in key tech-intensive sectors such as software, computer services, pharmaceuticals, and biotechnology. Moreover, China and other emerging nations are rapidly catching up, dramatically diminishing the EU's relative economic and political influence on the global stage. The urgency for the EU to bridge these gaps is more critical than ever. The EU's profound investment gap highlights a systemic advantage for the US in fostering innovation and economic growth. The EU's regulatory complexity, largely driven by legal fragmentation in horizontal policies, further exacerbate the situation, deterring cross-border activities reducing the region's attractiveness to global investors.
Keywords: 330